1986
DOI: 10.1002/bjs.1800730919
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management of penetrating liver injuries: A prospective study

Abstract: This is a report of a study of 63 cases of penetrating liver injuries. Forty-two patients (67 per cent) who presented with signs of an acute abdomen were operated on. The liver was routinely sutured and drained. There was no incidence of postoperative intra-abdominal sepsis or haematobilia. In the remaining 21 patients (33 per cent) liver involvement was suggested by the fact that the wound was over the liver region, and penetrated the peritoneum, and abdominal paracentesis for blood was positive or the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 7 publications
0
27
0
2
Order By: Relevance
“…2,3,11,14 -16 Even when peritoneal or retroperitoneal penetration of bullets and organ damage is revealed on imaging, studies have demonstrated that injured organs (e.g., liver, kidney) and injury patterns can be safely managed nonoperatively. [17][18][19][20][21] This approach of selective nonoperative management of both blunt and penetrating abdominal trauma has resulted in an acceptably low incidence of missed injuries, delayed diagnosis, and deaths. 1,22 Demetriades and Velmahos, in their review article on the "emerging era of nonoperative management", emphasize that this strategy re- …”
Section: Discussionmentioning
confidence: 99%
“…2,3,11,14 -16 Even when peritoneal or retroperitoneal penetration of bullets and organ damage is revealed on imaging, studies have demonstrated that injured organs (e.g., liver, kidney) and injury patterns can be safely managed nonoperatively. [17][18][19][20][21] This approach of selective nonoperative management of both blunt and penetrating abdominal trauma has resulted in an acceptably low incidence of missed injuries, delayed diagnosis, and deaths. 1,22 Demetriades and Velmahos, in their review article on the "emerging era of nonoperative management", emphasize that this strategy re- …”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of evidence supporting SNOM is derived from studies of 'all comers' with penetrating abdominal trauma, it is worth noting that one of the earliest prospective studies of SNOM exclusively recruited patients with presumed isolated liver injuries. 18 In contrast, our study cohort was not a homogenous group of isolated liver injuries. Concomitant thoracic and hollow visceral injuries were present in 25% and 16% of cases respectively.…”
Section: Discussionmentioning
confidence: 85%
“…These patients were carefully observed in the surgical unit with a CT scan at 48 h confirming the absence of hemoperitoneum: a subcapsular hematoma did not extend after 1 week's monitoring. The nonoperative observation of hepatic injuries can now be an alternative, thanks to modern technology (ultrasonography, CT scan) if the patient is hemodynamically stable, if there is no doubt about another intraabdominal injury and if the hemoperitoneum is absent [6,7] or minimal [13]. It involves an initial admission to the intensive care unit of the surgical department with careful attention to vital signs, abdominal examination and CT scanning for 10 days, and immediate laparotomy is indicated if continuous bleeding occurs secondarily.…”
Section: Discussionmentioning
confidence: 99%